2017
DOI: 10.1111/bjd.15241
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of leg-ulcer healing in sickle cell disease: a multicentre, prospective cohort study

Abstract: SCD-LU complete healing is independently associated with the clinical characteristics of LUs rather than the clinical or biological characteristics of SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
30
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 38 publications
(71 reference statements)
7
30
0
6
Order By: Relevance
“…Our analysis identified that duration over 90 days and wound area >10 cm 2 are predictors of poor outcome for sickle cell ulcers. This is consistent with previous studies, which were conducted within highvolume sickle cell disease referral centers, 7,12 and confirms that these findings are applicable to a broader population treated in wound healing centers. Our findings confirmed a significant age difference between patients with sickle cell ulcers and those with venous ulcers, 42.2 years versus 70.7 years, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our analysis identified that duration over 90 days and wound area >10 cm 2 are predictors of poor outcome for sickle cell ulcers. This is consistent with previous studies, which were conducted within highvolume sickle cell disease referral centers, 7,12 and confirms that these findings are applicable to a broader population treated in wound healing centers. Our findings confirmed a significant age difference between patients with sickle cell ulcers and those with venous ulcers, 42.2 years versus 70.7 years, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Although the data set did include frequency of visits and of debridements, additional data on treatment approaches for sickle cell ulcers-such as topical treatments, compression therapy, human skin equivalents, skin grafts, transfusion therapy, nutritional support, antibiot-ics, or pentoxifylline-were not available. 9,12 The analysis focused on healing within individual care episodes, and could not discern between wound recurrence and wound persistence. Finally, the analysis does not clarify to what degree larger area and longer duration at presentation are markers for intrinsically poorer healing processes in the patient, as opposed to markers of poor or delayed initiation of care that leads to worse healing prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one separates those who will never have ulcers from those who will. The second separates patients who will not be able to heal ‘quickly’ from others that Senet et al . have identified here.…”
mentioning
confidence: 85%
“…In this issue of the BJD Senet et al . have questioned the factors that may predict the course of ulcers in patients with sickle cell disease (SCD) . Through a retrospective analysis from two French referral centres, these authors found that two parameters were predictive of a poor prognosis: a duration of ulcers at inclusion longer than 9 weeks and a surface area larger than 8 cm 2 .…”
mentioning
confidence: 99%